Combined convective transport of brinkman-viscoelastic fluid across horizontal circular cylinder with convective boundary condition - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Syazwani, Mohd Zokri; Mohd Rijal, Ilias (Semarak Ilmu Publishing, 2022)
Traditional heat transfer fluids frequently encounter several limitations in the heat transfer process, due to the lower thermal conductivity in heat transfer process industries, and also has an impact on the performance of heat transfer in industrial sectors. In order to overcome the problem, researchers have currently considered an alternative development of heat transfer of fluids. Hence, this study will concentrate on the problem of steady combined convective transport. In particular, the flow of Brinkman-viscoelastic fluid over a horizontal circular cylinder with the influence of convective boundary condition (CBC) was investigated. Using the necessary similarity transformation, the governing equations were converted into a less complicated form and numerically solved by using Runge-Kutta-Fehlberg-method, which was programmed in Maple software. The influence of Biot number, combined convection, Brinkman and viscoelastic parameters are analyzed and demonstrated in graphs and tables. Numerical result showed that the fluid velocity increased with improving conjugate and combined convection parameter, but decreased with increasing Brinkman and viscoelastic parameter. It is also discovered the reverse trend on temperature profiles.